1982
DOI: 10.1007/978-1-349-16939-9
|View full text |Cite
|
Sign up to set email alerts
|

The Rules of Sociological Method

Abstract: This series aims to create a forum for debate between different theoretical and philosophical traditions in the social sciences. As well as covering broad schools of thought, the series will also concentrate upon the work of particular thinkers whose ideas have had a major impact on social science (these books appear under the subseries title of 'Theoretical Traditions in the Social Sciences'). The series is not limited to abstract theoretical discussion -it will also include more substantive works on contempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
1,353
2
87

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,941 publications
(1,452 citation statements)
references
References 0 publications
10
1,353
2
87
Order By: Relevance
“…But process refers to culture's emergent or continuous re-production of itself (Garfinkel, 1967). Durkheim's (1938) necessity of cultural reproduction -conformity (or improvement) through change -was morphological, not evolutionary (Jenks 1993) and fits with Levi Strauss' (1964) metaphor of lived culture as a geological topography. This cultural topography-in-change is explained by Bourdieu (1971) as "Habitus and Field" where "Field" is a set of social relationships.…”
Section: Definition Of Culturesupporting
confidence: 63%
See 1 more Smart Citation
“…But process refers to culture's emergent or continuous re-production of itself (Garfinkel, 1967). Durkheim's (1938) necessity of cultural reproduction -conformity (or improvement) through change -was morphological, not evolutionary (Jenks 1993) and fits with Levi Strauss' (1964) metaphor of lived culture as a geological topography. This cultural topography-in-change is explained by Bourdieu (1971) as "Habitus and Field" where "Field" is a set of social relationships.…”
Section: Definition Of Culturesupporting
confidence: 63%
“…His method is called "thick description." Durkheim (1938) compared structure with process. The standard normative expectations held collectively -while not fixedprovide the weight of social consensus that defines a social group.…”
Section: Definition Of Culturementioning
confidence: 99%
“…also Durkheim 1982, of whom the later Davies was a critic, while his earlier work was and to some degree all his work remained staunchly Durkheimian). Thus, as Davies reminds us insistently in practically all of his contributions to humour research, research statements, like jokes, are more fully understood in the context of other social facts.…”
Section: Methodsmentioning
confidence: 99%
“…Landman (2003) suggested that making comparisons is the essence of human nature. For Durkheim (1938), "comparative sociology is not a particular branch of sociology: it is sociology" (p. 139). It is, perhaps, for this reason that Øyen (2004) suggests that all "social science is based on comparisons, whether it is comparisons between different groups, different social phenomena or different process" (p. 278).…”
Section: Introductionmentioning
confidence: 99%